Pola Asuh orang tua dalam memotivasi belajar anak di RA.Dharma Wanita Kemenag Kabupaten Jeneponto - Anita Wardani; Muhammad Asri; Rahmawati Rahmawati; Muhaemin B; Latang Latang (UNIVERSITAS NEGERI MAKASSAR, 2026)
This research examines parenting patterns in motivating children's learning at RA.Dharma Wanita, Ministry of Religion, Jeneponto Regency. The research subjects were 3 people consisting of parents, school principals and educators/teachers. Data was collected through observation, interviews and documentation. The data was processed through data reduction procedures, data presentation, and drawing conclusions and verification. The research results showed that there are several parenting patterns in motivating children's learning, including 1). As Motivators, parents understand the child's personality and provide attention and enthusiasm for learning, thereby generating the child's learning motivation. 2). As managers, in this case parents, so that children do not get stressed in learning, parents provide the learning facilities they need and give gifts and words of praise.